Optimalisasi Keterampilan Menulis Melalui Pembelajaran Holistik pada Siswa Kelas III di SDN 6 Bandar Baru - Fajriah; Husni Rahmah (Al-Faiza : Journal of Islamic Education Studies, 2024)
Writing skills in elementary school will form basic skills that affect writing skills at the next level. Writing learning is expected to shape elementary school students to be able to communicate well in writing in their lives. The purpose of this study was to find out how to optimize the difficulties in writing skills in Holistic learning for grade III students of SDN 6 Bandar Baru. This study used Classroom Action Research (CAR). The subjects of this study were 16 students in grade III consisting of 9 males and 7 females. This study used two cycles in the first cycle consisting of two meetings, while the second cycle was one meeting. Data collection techniques through observation of portfolio sheets and documentation. Data analysis techniques in the form of CAR to determine the effect of holistic learning methods on students. Based on the data analysis, it is known that after using holistic learning, learning outcomes were applied. This can be seen from the increase in learning completeness in students in Cycle I, the average completeness obtained was 63.25%, as many as 8 students exceeded the KKM in Cycle II, the average Post Test completeness was 88%, as many as 15 students exceeded the KKM. In this case, it can be proven that there is an increase in the percentage of cycle I and cycle II, which is 25%. So it can be concluded that the use of the Holistic Learning method can improve the activity and learning outcomes of class III students of SDN 6 Bandar Baru.